Is tranexamic acid exposure related to blood loss in hip arthroplasty? A pharmacokinetic–pharmacodynamic study. (28th November 2017) - Lanoiselée, Julien; Zufferey, Paul J.; Ollier, Edouard; Hodin, Sophie; Delavenne, Xavier; ,
Abstract : Aims: Tranexamic acid (TXA) is an antifibrinolytic agent, decreasing blood loss in hip arthroplasty. The present study investigated the relationship between TXA exposure markers, including the time above the in vitro threshold reported for inhibition of fibrinolysis (10 mg l −1 ), and perioperative blood loss. Methods: Data were obtained from a prospective, double‐blind, parallel‐arm, randomized superiority study in hip arthroplasty. Patients received a preoperative intravenous bolus of TXA 1 g followed by a continuous infusion of either TXA 1 g or placebo over 8 h. A population pharmacokinetic study was conducted to quantify TXA exposure. Results: In total, 827 TXA plasma concentrations were measured in 166 patients. A two‐compartment model fitted the data best, total body weight determining interpatient variability in the central volume of distribution. Creatinine clearance accounted for interpatient variability in clearance. At the end of surgery, all patients had TXA concentrations above the therapeutic target of 10 mg l −1 . The model‐estimated time during which the TXA concentration was above 10 mg l −1 ranged from 3.3 h to 16.3 h. No relationship was found between blood loss and either the time during which the TXA concentration exceeded 10 mg l −1 or the other exposure markers tested (maximum plasma concentration, area under the concentration–time curve). Conclusion: In hip arthroplasty, TXA plasma concentrations were maintained above 10 mg l −1 during surgery and for a minimum of 3 h with a preoperative TXA dose of 1 g. Keeping TXA concentrations above this threshold up to 16 h conferred no advantage with regard to blood loss.